Futures images of woodchips as an energy source in Finland - Mäkelä Marileena; Parkkinen Marjukka; Lyytimäki Jari; Nygrén Nina A. (Elsevier, 2022)
Wood is the most widely used renewable energy source in the world. However, there are competing views on how wood should be used in the future. The objective of this study is to examine conceptions related to alternative futures for the use of woodchips as an energy source in Finland. We construct futures images based on two data sources describing the views favouring the use of woodchips: thematic interviews with woodchip users and newspaper articles. The futures images are constructed based on two key themes that emerge from our data. First, the alternatives are imagined for the types of the operators using woodchips in the future, varying between small- and large-scale use. Second, the strong role of regulations, particularly at the European Union level, will be the key driver of the future use of woodchips as an energy source. The results show wide variation in the potential goals of public governance, ranging from regulations designed to strongly support the use of woodchips as an energy source to almost complete conservation of forests. Focusing on the regime level, we identify possible transition pathways illustrating how the use of woodchips could change in the future and discuss possible policy implications.